HPV-16 E7-Specific Cellular Immune Response in Women With Cervical Intraepithelial Lesion Contributes to Viral Clearance: A Cross-Sectional and Longitudinal Clinical Study - Zhang, Lina; Shi, Xinyi; Zhang, Qing; Mao, Zhilei; Shi, Xiaoyu; Zhou, Jun; Jian, Aili; Zhu, Renying; Jiang, Shisong; Lu, Wenshu (Frontiers in Immunology, 2022)
High-risk human papillomavirus (HPV) infection is the cause of almost all cervical cancers. HPV16 is one of the main risk subtypes. Although screening programs have greatly reduced the prevalence of cervical cancer in developed countries, current diagnostic tests cannot predict if mild lesions may progress into invasive lesions or not. In the current cross-sectional and longitudinal clinical study, we found that the HPV16 E7-specific T cell response in peripheral blood mononuclear cells of HPV16-infected patients is related to HPV16 clearance. It contributes to protecting the squamous interaepithelial lesion (SIL) from further malignant development. Of the HPV16 infected women enrolled (n=131), 42 had neither intraepithelial lesion nor malignancy (NILM), 33 had low-grade SIL, 39 had high-grade SIL, and 17 had cervical cancer. Only one of 17 (5.9%) cancer patients had a positive HPV16 E7-specific T cell response, dramatically lower than the groups of precancer patients. After one year of follow-up, most women (28/33, 84.8%) with persistent HPV infection did not exhibit a HPV16 E7-specific T cell response. Furthermore, 3 malignantly progressed women were negative to the HPV16 E7-specific T cell response. None of the patients with a positive HPV16 E7-specific T cell response progressed to further deterioration. Our observation suggests that HPV16 E7-specific T cell immunity is significant in viral clearance and contributes in protection against progression to malignancy.